"Political disobedience and the climate emergency". (July 2022) - Scheuerman, William E.
Climate activists have recently engaged in widely publicized acts of politically motivated lawbreaking. This article identifies and critically analyzes two seemingly overlapping but in fact diverging approaches among present-day activists. Though their illegal acts (e.g., blockades, occupations, and selective property damage) sometimes appear equivalent, the rival approaches place them in contrasting lights; the resulting differences are normatively and politically consequential. The first and now predominant approach favors nonviolent civil disobedience, understood in conventional terms as civil, conscientious, nonviolent, public lawbreaking. Though this approach exhibits many strengths, its proponents sometimes rely on problematic usages of recent political science scholarship that cannot withstand critical scrutiny. The second approach views nonviolent civil disobedience as insufficiently militant and instead aims primarily to block and disrupt our fossil fuel-driven political economy. Its preferred mode of political illegality is sabotage. Less concerned than the first approach with altering public opinion, it generally writes off the prospect of meaningful political reform. Though both approaches rely on the idea of a "climate emergency" to justify their activities, the second approach provides a vivid warning of its possible dangers. Although the momentous threats posed by global warming are undeniable, the idea of a climate emergency risks opening the door to political avant-gardism and, potentially, authoritarianism.